To solve the quadratic equation n^2 + 2n - 24 = 0 by factoring, we need to find two numbers that multiply to -24 and add up to 2.
The two numbers that satisfy this condition are 6 and -4, because 6 * -4 = -24 and 6 + (-4) = 2.
So, we can rewrite the equation as:
n^2 + 6n - 4n - 24 = 0
Now, we can factor by grouping:
n(n + 6) - 4(n + 6) = 0
(n - 4)(n + 6) = 0
Now, we can set each factor to zero and solve for n:
n - 4 = 0 or n + 6 = 0
n = 4 or n = -6
Therefore, the solutions to the equation n^2 + 2n - 24 = 0 are n = 4 and n = -6.
Solve by factoring n^2 + 2h - 24 = 0
1 answer